Laughter therapy for the risk of violent behaviour in people with severe mental disorders: A case study report - Syalsabillah, Padila Putri; Dekawaty, Ayu (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The risk of violent behaviour is an angry response that can arise and can injure oneself, others, and the environment. Laughter therapy has become one of the complementary approaches believed to reduce emotional tension and help control anger. Purpose: To analyse laughter therapy in reducing the risk of violent behaviour in people with severe mental disorders. Method: A qualitative approach method with the Case Study Research (CSR) strategy. Results: There was a decrease in scores on the observation sheet of signs and symptoms in patients at risk of violent behaviour, with the score before laughter therapy being 8 and decreasing to 2 after laughter therapy was administered. Conclusion: Laughter therapy is one of the non-pharmacological therapies to reduce anger, especially in patients at risk of violent behaviour. Keywords: Laughter Therapy; Mental Health; Nursing Care; Risk of Violent Behaviour.